Therapy for thoracic lumbar and sacral vertebrae tumors using total spondylectomy and spine reconstruction through posterior or combined anterior-posterior approaches - YANG, PINGLIN (Oncol Lett, 2016)
The present study aimed to analyze the indications, feasibility, safety and clinical effects of total spondylectomy and spine reconstruction through posterior or combined anterior-posterior approaches for thoracic lumbar and sacral vertebrae tumors. Between December 2009 and May 2012, 10 patients with thoracic lumbar and sacral vertebrae tumors were retrospectively analyzed. Different surgical indications and approaches were used according to the affected segments, the extent of lesion involvement and the specific pathology results. One-stage posterior or combined anterior-posterior total spondylectomy and reconstruction was used for the treatment of complicated thoracic lumbar and sacral vertebral malignant tumors and invasive benign tumors. The duration of surgery, levels of intraoperative blood loss and transfusions, and the clinical effects were observed. The average surgical duration was 6.8 h (range, 4.8–12 h), with an average blood loss level of 3,200 ml (range, 1,500–10,000 ml) and an average transfusion level of 2,500 ml. During the average 15 months (range, 3–29 months) follow up, two patients succumbed and one patient experienced tumor recurrence. Neither tumor reoccurrence nor metastasis was observed in all other patients. Personalized surgical indications and approaches according to the affected segments, the extent of lesion involvement and the specific pathology results would aid in the reduction of pain, the improvement of nerve function and the reduction of tumor recurrence.